The effect of photoperiod, environmental temperature and wind speed on external quality of free-range turkey eggs - José Ignacio Salgado Pardo; Juan Vicente Delgado Bermejo; Antonio González Ariza; José Manuel León Jurado; María Esperanza Camacho Vallejo (PLoS ONE, 2025)
Due to the lack of research in free-range poultry, the influence of environmental factors on laying remains underdeveloped nowadays. Therefore, the present study aimed to determine the influence of meteorological events and the moon cycle on the weight and shape index of turkey eggs produced in alternative systems. To this aim, 194 eggs laid by Andalusian turkey hens raised outdoors were collected and daily measured for 14 months. Seven categories were obtained attending to their weight (heavy, medium, and light) and shape index (sharp, standard, and round), and performed as dependent variables in the discriminant canonical analysis (DCA). As explanatory variables, meteorological and moon cycle features were collected from repositories consulting the day before each egg was laid. Minimum pressure, moon phase, and maximum temperature reported multicollinearity problems (VIF > 5.0) and were removed from further analysis. Moderate correlations among climatic variables influencing egg quality were found and ranged from + 0.574 to – 0.537, involving maximum gust speed in both cases. Variables exhibiting explanatory power in the DCA were sunshine hours (λ = 0.691, F = 13.950), minimum temperature (λ = 0.874, F = 4.476), and maximum gust speed (λ = 0.944, F = 1.841). Results evidence alternative productions present a different environmental exposure than indoors, as well as highlight the suitability of this breed for free range systems.